2018
DOI: 10.1182/blood-2018-99-111429
|View full text |Cite
|
Sign up to set email alerts
|

Significant Differences in Test Availability and Access to Novel Drugs for Multiple Myeloma between Public and Private Hospitals in Latin America. Grupo De Estudio Latinoamericano De Mieloma Multiple (GELAMM)

Abstract: Introduction Compliance with Multiple Myeloma (MM) recommendations regarding diagnosis and treatment is highly variable worldwide, outside clinical trials. This survey among hematologists from Latin America (LA) aims to describe real access to diagnostic and prognostic analyses and first line treatment for newly diagnosed MM (NDMM). Objectives To describe the access to diagnostic and prognostic tests and first line treatment options for MM in LA. To c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…This score uses the tumor burden and disease biology, creating a unified prognostic index; however, lack of standardization, limited availability, and cost of iFISH are factors against its widespread use in real practice. A recent report from the Latin American Myeloma Group (GELAMM) focusing on access to diagnostic analysis in 13 countries showed that iFISH was available in only 32% of the public and 67% of private institutions [ 6 ]. Also, in most institutions, no plasma cell sorting is done [ 6 ].…”
Section: Background and Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…This score uses the tumor burden and disease biology, creating a unified prognostic index; however, lack of standardization, limited availability, and cost of iFISH are factors against its widespread use in real practice. A recent report from the Latin American Myeloma Group (GELAMM) focusing on access to diagnostic analysis in 13 countries showed that iFISH was available in only 32% of the public and 67% of private institutions [ 6 ]. Also, in most institutions, no plasma cell sorting is done [ 6 ].…”
Section: Background and Aimsmentioning
confidence: 99%
“…A recent report from the Latin American Myeloma Group (GELAMM) focusing on access to diagnostic analysis in 13 countries showed that iFISH was available in only 32% of the public and 67% of private institutions [ 6 ]. Also, in most institutions, no plasma cell sorting is done [ 6 ].…”
Section: Background and Aimsmentioning
confidence: 99%
“…Sin embargo, en países en vías de desarrollo, como los países latinoamericanos el acceso a herramientas diagnósticas como FISH puede ser limitado. Esto fue evidenciado por el Grupo de Estudio Latinoamericano de Mieloma Multiple (GELAMM), quienes reportaron para esta región, que el acceso a iFISH varía del 32.6% en las instituciones públicas al 67% en las privadas, y la disponibilidad de citogenética convencional varía del 41.7% en las instituciones públicas al 85.6% en las privadas, dificultando así el uso extendido de R-ISS [11]. De forma más desalentadora, un estudio realizado en siete países de América Latina evidenció que el 31.9% de los pacientes incluidos no tenían documentado su estadio ISS, lo que refleja la relativa falta de acceso, incluso a la cuantificación de beta 2 microglobulina [12].…”
Section: Registro Nacional De Tumoresunclassified